Mechanism of low frequency high amplitude pressure fluctuation in a pump-turbine during the load rejection process - Fu, Xiaolong; Zuo, Zhigang; Chang, Hong; Li, Deyou; Wang, Hongjie; Wei, Xianzhu (Journal of hydraulic research, 2021)
Owing to the complexity of the load rejection process, the accompanied complex low frequency pressure fluctuations and their sources have not been determined. Herein, the load rejection transient process of a pump-turbine was simulated with a three-dimensional (3-D) large eddy simulation method and a dynamic mesh technology. The simulation results were validated against the experimental data. Through the joint time-frequency analysis of simulated pressure, the complex low frequency pressure fluctuation components were captured, which are generally lower than the rated rotational frequency of the runner. A comprehensive formation mechanism of these complex low frequency pressure fluctuation components was attributed to three transient hydraulic phenomena and their interactions: the water hammer in the pump-turbine, local reverse flow near the runner inlet, and 3-D blocking water ring in the vaneless space. These findings facilitate the elucidation and elimination of complex low frequency high amplitude pressure fluctuations during the load rejection transient process.